Teaching vocabulary Teaching vocabulary with the help of visual aids - Falvai Viktória; Orosz Andrea (2001)
Teaching vocabulary is essential as it is one of the most important conditions of the ability to communicate. The teacher should teach not only the meaning of the words and expressions but also their usage, formation and grammar not to mention how they are presented. Visuals are important appliances in the process of teaching words and phrases because they have an influence on students' emotions, awake and hold their interest creating a positive attitude to learning. It is widely known that learning is more effective when learners get stimuli several ways. I try to verify that if students not only hear the words and their meanings but also see pictures, realia, drawings they can remember them better.
Keywords: Pedagógusképzés